ESTIMATION OF ABUNDANCE FOR THE MIGRATING JUVENILE PINK SALMON IN THE RIVERS OF SAKHALIN AND ITURUP ISLANDS IN 2019 - A. M. Kaev; G. N. Dzen; P. S. Sukhonos; I. S. Bobrov (Известия ТИНРО)
Number of the pink salmon fry migrating downstream from their spawning grounds in the control rivers in 2019 is assessed as 17546.2 . 103 and 14795.7 . 103 ind. for the Dagi and Bolshoi Khuzi Rivers (northeastern Sakhalin), as 89.1 . 103 and 2636.1 . 103 ind. for the Poronai River tributaries — the Kholodny and Orlovka, as 2759.8 . 103 and 21456.0 . 103 ind. for the Lazovaya and Pugachevka Rivers (western coast of the Patience/Terpeniya Bay), as 5803.8 . 103 and 19020.0 . 103 ind. for the Voznesenka and Ochepuha Rivers (southeastern Sakhalin), as 1822.4 . 103 and 2139.0 . 103 for the Taranai and Kura Rivers (Aniva Bay coast), and as 15834.1 . 103 and 7626.1 . 103 ind. for the Rybatskaya and Olya Rivers (Iturup Island), respectively. In all areas, the pink juveniles migrated from the spawning grounds earlier than usual, obviously because of accelerated development of the embryos in conditions of abnormally warm autumn. The number of juveniles migrated from all spawning grounds in the rivers of respective regions is estimated taking into account the escapement of pink salmon spawners and the downstream migration index determined for the control rivers (ratio of the spawners escapement and the number of subsequent downstream migrating juveniles): the total number for the natural spawning grounds is estimated as 1168.9 . 106 ind. for the rivers of the eastern coast of Sakhalin (including the Aniva Bay) and 471.1 . 106 ind. for the rivers of Iturup Island (Okhotsk Sea coast). Additional 141.3 . 106 ind. were released from artificial hatcheries of eastern Sakhalin and 122.0 . 106 ind. — from artificial hatcheries of Iturup Island. The downstream migration is considered as highly abundant for northeastern Sakhalin and Iturup Island, but is insufficiently abundant for the Patience/Terpeniya Bay and Aniva Bay where the landings of this generation should be limited. The pink salmon return to southeastern Sakhalin in 2020 is expected to be better than in 2018 due to satisfactory abundance of the juveniles from natural spawning grounds.